Nonreciprocal sideband responses in a spinning microwave magnomechanical system - Wang, Xin; Huang, Kai-Wei; Xiong, Hao (Optics express, 2023)
Nonreciprocal sideband responses in a spinning microwave magnomechanical system consists of a spinning resonator coupled with a yttrium iron garnet sphere are proposed. We show that the efficiency of sideband generation can be enhanced in one driving direction but restrained in the opposite. This nonreciprocity results from Sagnac effect induced by the spinning resonator, leading to asymmetric magnonic responses in two different driving directions. Beyond the conventional linearized description, the properties of nonreciprocal two-color second-order sideband are demonstrated. By adjusting Sagnac-Fizeau shift and the power of control field, the degree of asymmetric magnonic responses can be strengthened, therefore causing stronger nonreciprocity of sideband. Especially, for the case of strong Sagnac-Fizeau shift and the control field, high level of efficiency and isolation ratio of sideband are achieved simultaneously and the operational bandwidth of strong nonreciprocity can be expanded. Our proposal provides an effective avenue for the manipulation of the nonreciprocity of sideband and has potentially practical applications in on-chip microwave isolation devices and magnon-based precision measurement.